2018
DOI: 10.1007/s00401-018-1947-3
|View full text |Cite
|
Sign up to set email alerts
|

Seeding selectivity and ultrasensitive detection of tau aggregate conformers of Alzheimer disease

Abstract: Alzheimer disease (AD) and chronic traumatic encephalopathy (CTE) involve the abnormal accumulation in the brain of filaments composed of both three-repeat (3R) and four-repeat (4R) (3R/4R) tau isoforms. To probe the molecular basis for AD’s tau filament propagation and to improve detection of tau aggregates as potential biomarkers, we have exploited the seeded polymerization growth mechanism of tau filaments to develop a highly selective and ultrasensitive cell-free tau seed amplification assay optimized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 47 publications
11
131
1
Order By: Relevance
“…To our knowledge, no studies have been reported to selectively detect misfolded tau seeds from AD brains using recombinant full-length tau isoforms as substrates. Our study complements a recent investigation describing ultrasensitive detection of tau aggregate conformer of AD with a mixture of two significantly shortened tau fragments as dual substrates (Kraus et al, 2019). The successful seeding activities of AD brain homogenates with individual tau isoforms as a substrate further validated the predicted presence of all six misfolded tau isoforms in AD brains (Goedert et al, 1992;Lee et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…To our knowledge, no studies have been reported to selectively detect misfolded tau seeds from AD brains using recombinant full-length tau isoforms as substrates. Our study complements a recent investigation describing ultrasensitive detection of tau aggregate conformer of AD with a mixture of two significantly shortened tau fragments as dual substrates (Kraus et al, 2019). The successful seeding activities of AD brain homogenates with individual tau isoforms as a substrate further validated the predicted presence of all six misfolded tau isoforms in AD brains (Goedert et al, 1992;Lee et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…RT-QuIC assay has been used for detection of seeding activities of misfolded proteins, first for prions and then for aSyn and tau in vitro (Atarashi et al, 2008;Orru et al, 2017;Groveman et al, 2018;Sano et al, 2018;Saijo et al, 2017;Kraus et al, 2019). To determine whether various recombinant wild-type human tau isoforms can be converted by the tau aggregate seeds from AD brain samples, we detected autopsied AD and non-AD brain samples from neuropathologically confirmed cadavers (Table 1).…”
Section: Full-length Tau Isoform Based Rt-quic Assay Selectively Detementioning
confidence: 99%
See 2 more Smart Citations
“…A recently described technique called real-time quaking-induced conversion, which exploits the ability of prion protein to induce self-aggregation, has been used to develop a diagnostic CSF test for Creutzfeldt-Jakob disease (145). This method has now also been developed into a test to detect pathological forms of tau in CSF from patients with AD or other tauopathies (146,147). Seedcompetent high-molecular-weight tau species have been detected in human CSF (78), but there is yet no established method in clinical laboratory practice.…”
Section: Measures Of Tau In Body Fluidsmentioning
confidence: 99%